Budaya Kualitas Pada Organisasi Yang Berkualitas - Damayanti, Retno Wulan (Performa: Media Ilmiah Teknik Industri, 2007)
One of the biggest barier which faced by company to apply total quality is cultural barricade. Many company try to implement total quality , entangling employees at all level with providing training to guarantee employees to be skilled, where this matter is done just to flatten their ability. There is no effort to make a freshment in doing something. In other words, there is no effort to change company culture.